Integrasi Teknologi Blockchain untuk Kontrol Akses yang Aman dalam Basis Data Terdistribusi - Riffal Setiawan; Tata Sutabri (JOURNAL SAINS STUDENT RESEARCH, 2025)
Nowadays, more and more digital systems are using distributed databases to store and manage information. This kind of system does make data easier to access from anywhere, but on the other hand, there are also security issues, especially regarding who can access the data. This is where blockchain technology is starting to be noticed. This technology is known for having a secure and transparent structure, so it is considered to be able to help solve the access control problem.This study tries to see to what extent blockchain can be integrated to manage access control in distributed databases. The study was conducted through literature analysis from various relevant scientific references. The results showed that blockchain can provide solutions through features such as smart contracts and consensus systems that make the data access process more controlled and difficult to manipulate. However, there are still challenges, such as speed, cost, and technical implementation that is not always simple.Therefore, a flexible approach is needed perhaps a combination of blockchain and a regular data system so that security is maintained but the system can still run efficiently.